The Evaluation of the CIPP Model in The Implementation of Character Education at Junior High School - W, Yuliana Retno Dwi; Haryono, Hartono; Florentinus, Totok Sumaryanto (Innovative Journal of Curriculum and Educational Technology, 2018)
St. Francis Junior High School Kayu Putih has the idealsin line with the goals of national education, the formation of character towards a dignifiednation of civilization. The age of students in junior high school is a transitional age, therefore,need a particular approach technique to bring out good charactersfor them. The purpose of this study is to analyze the basis of character education preparation, supporting resources, implementation of character educationand character educationachievementin St. Francis Junior High School.Kayu Putih, East Jakarta. This study is a CIPP model evaluation research that effectivefor making decisions forimproving the program. The subjects were principals, deputy principals of curriculum, teachers, parents, the graduates, and students. The primary data collected using observation and interviews, whereas, the secondary data was takenfrom the documentation. We use qualitative data to analyze. The results showthat: (1) the basis for the preparation of character education is well structured, but lacking for the aspects of school policy, (2) the supporting resources were sufficient,however,needtheteachers to assist students with special cases, (3) the implementation of the character education was still under-evaluated in each of its activities, (4) for the achievement of the character education, students less able to interpret events and actions related to moral feelings.Generally, this study is beneficial for schools, teachers, parents, governments, and researchers to create innovation in the implement and make policy regard to the program of character education, especially for religious-based schools.